النظام القانوني لتداول الأسهم في شركة المساهمة - نورالدين, شبرو (جامعة الوادي University of Eloued, 2019)
"تخضع الأسهم لمبدأ حرية التداول، وتختلف طريقة تداوله بتغير شكل الإصدار فالأسهم الإسمية تتداول عن طريق القيد في سجل الشركة، وعن طريق التسليم إذا كان السهم لحامله، إذ تعني قابلية التداول للسهم في شركة المساهمة جواز تنازل الشريك عن حصته للغير دون أن يؤثر ذلك على رأسمال الشركة أو بقائها. وحدود مبدأ حرية تداول الأسهم تتمثل في قیود مؤقتة يقصد بها تنظیم التداول وهي القيود القانونية التي قررها المشرع والقيود الاتفاقية التي ينص عليها في القانون الأساسي للشركة، كما تتعرض الأسهم لبعض المعوقات كالحجز او الرهن و تعرض الأسهم لخطر الضیاع أو السرقة. ""The shares are subject to the principle of freedom of trading. The way of trading varies according to the format of the shares; The nominal shares are traded through the registration in the company's register and by delivery if the share is to the holder whiteout affect the Company or its survival. The limits of the principle of free circulation of shares are temporary restrictions that are intended to regulate trading and There are the legal restrictions determined by the legislator and the restrictions stipulated in the company's articles of association; The stock is also subject to certain obstacles such as seizure or foreclosure and exposure to risk of loss or theft. "
ماستر اعمال
Keywords: الأسهم ، تداول_الأسهم ، مبدأ_تداول_الأسهم ، القيود ، المعوقات; The shares ; the principle of freedom of trading ; restrictions ; obstacles .